Solar Radio Burst Type II characteristics and Coronal Mass Ejections (CMEs) structure based on the presence of a moreton wave - Z.S. Hamidi; N.H. Zainol; N.N.M. Shariff; N. Mohamad Ansor (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Moreton wave has been extensively studied in explaining the relation between solar flare, Coronal Mass Ejections (CMEs) and Solar Radio Solar Burst Type II (SRBT II) phenomena. The purpose of this study was to determine whether Moreton waves have an impact on CME structure based on SRBT II parameters. The drift rate and structures of 28 SRBT II events selected from year 2014 to 2017 and observed by using ground-based Compound Low-cost Low Frequency Transportable Observatory (CALLISTO) spectrometer were determined. The CME data such as width angle and velocity were obtained from Large Angle Spectroscopy Coronagraph Observatory (LASCO) instrument, while solar flare class and its Active Region (AR) were attained from the Geostationary Operational Environmental Satellite (GOES). From the results, impulsive CME events have X, M and C class of solar flare in the presence of Moreton wave by using GONG data archive while gradual CME were associated with C or B class of solar flare. Impulsive CMEs have an angle of width more than 60° and velocity more than 500 km/s associated with both herringbone (HB) and harmonic structure of SRBT II. However, 30% of gradual CMEs which are associated with HB structure of SRBT II did not accompany by Moreton wave presence. Therefore, we can deduce that the impulsive CMEs are formed under the influence of Moreton wave and gradual CMEs emerged without the Moreton wave, based on the structure of SRBT II.